2015
DOI: 10.3109/09513590.2015.1103221
|View full text |Cite
|
Sign up to set email alerts
|

Essure a novel option for the treatment of hydrosalpinx: a case series and literature review

Abstract: Essure(®) placement is an alternative method for occlusion of hydrosalpinges before IVF. Monitoring the live-birth rate confirms that this option may be considered when laparoscopy is impossible or contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The other four studies were included in our analysis. Moreover, we included four additional studies that were not considered in that review. The miscarriage rate reported in the previous review (25.9%) is lower than that of our study (38%).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The other four studies were included in our analysis. Moreover, we included four additional studies that were not considered in that review. The miscarriage rate reported in the previous review (25.9%) is lower than that of our study (38%).…”
Section: Discussionmentioning
confidence: 52%
“…Twenty‐six studies assessing the treatment of hydrosalpinx in women undergoing ET were included in our analysis. There were eight studies evaluating Essure; none of them was a randomized or even a prospective observational trial, and five evaluated only women who had a contraindication for laparoscopy. Overall, we observed that insertion of Essure prior to ET in women with hydrosalpinx is associated with a higher rate of miscarriage in comparison with other methods of treatment, without an improvement in clinical‐pregnancy or live‐birth rates.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[ 2 ] The current treatment options for hydrosalpinx mainly includes: salpingectomy, tubal proximal ligation, transvaginal aspirationat and salpingostomy, but only laparoscopic salpingectomy and tubal occlusion has proven to be effective to improve the outcome of IVF. [ 3 ] Currently, laparoscopic salpingectomy and tubal occlusion seem to be helpful to improve the success rate of IVF. Reproductive surgery is still necessary as a complementary treatment for optimizing IVF outcomes for patients with not only hydrosalpinges but also select cases of endometriomas and myomas.…”
Section: Introductionmentioning
confidence: 99%